BIG DATA IN HEALTHCARE: OPPORTUNITIES FOR IMPROVED PATIENT CARE AND SECURITY CONCERNS - Anas Alhur; Abdulaziz Alahmari; Aeshah alshowaiman; Dalal Alrowely; Faiz Alahmari; abdulkarim alahmari; Hamed alshamrani; Mohammed Alahmari; Ahmed Alahmari; Ali alshehri; Hadeel sanyour; Hassan asiri; et al. (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
This literature review explores the impact of big data in healthcare, focusing on its potential to improve patient care and the associated security risks. The study examines various big data applications, including predictive analytics, personalized medicine, and enhanced operational efficiencies, contributing to better diagnostics, treatment protocols, and patient outcomes. It also addresses significant security challenges such as data breaches, encryption practices, and compliance with data protection regulations. Through an analysis of articles from databases like PubMed and PsycINFO, the review identifies key themes and demonstrates how big data can revolutionize healthcare while presenting risks to privacy and system integrity. The findings highlight the need for collaboration among healthcare providers, policymakers, and technologists to leverage big data benefits in healthcare delivery securely.